Hubungan Kecerdasan Emosional Dan Motivasi Belajar Dengan Hasil Belajar IPA Peserta Didik Kelas VIII Kepulauan Selayar - Nelly Suryani Basri; Firdaus Daud (UNM Journal of Biological Education, 2022)
This study aims to determine: (1) the description of emotional intelligence, learning motivation, and science learning outcomes for students in class VIII SMPN in Benteng District, (2) The relationship between emotional intelligence and science learning outcomes for students in class VIII SMPN in Benteng Regency. Benteng Regency, (3) the relationship between learning motivation and science learning outcomes for class VIII SMPN students in Benteng Regency, (4) the relationship between emotional intelligence and learning motivation on science learning outcomes for VIII SMPN students in Benteng Regency. This research is an ex post facto research which is correlational. Sampling by means of random sampling. Data were analyzed by descriptive statistics and inferential statistical analysis. The conclusions in this study are as follows. (1) The emotional intelligence of class VIII SMP Negeri in Benteng Subdistrict, Selayar Islands Regency is in the medium qualification. Motivation to learn is in moderate to high qualifications, and student learning outcomes are in low, medium to high qualifications. (2) There is a significant influence of emotional intelligence directly on learning outcomes. (3) There is a significant effect of learning motivation directly on learning outcomes. (4) There is a significant influence between emotional intelligence and learning motivation together on learning outcome.